Equilibrium exchange rates in Southeastern Europe, Russia, Ukraine and Turkey: healthy or (Dutch) diseased? - Balázs Égert (Bank of Finland, Institute for Economies in Transition (BOFIT), 2005)
This paper investigates the equilibrium exchange rates of three Southeastern European countries (Bulgaria, Croatia and Romania), of two CIS economies (Russia and Ukraine) and of Turkey.A systematic approach in terms of different time horizons at which the equilibrium exchange rate is assessed is conducted, combined with a careful analysis of country-specific factors.For Russia, a first look is taken at the Dutch Disease phenomenon as a possible driving force behind equilibrium exchange rates.A unified framework including productivity and net foreign assets completed with a set control variables such as openness, public debt and public expenditures is used to compute total real misalignment bands.
URN:NBN:fi:bof-201408072020
Keywords: E31; O11; P17; 330; Balassa-Samuelson; Dutch Disease; Bulgaria; Croatia; Romania; Russia; Ukraine; Turkey